Antibacterial Activity Test on Face Toner Preparations 70% Ethanol Extract of Avocado Leaves (Persea americana Mill) Against Staphylococcus Aureus Bacteria - Wendy Mayasari Kalalo; Wahyu Purwanjani; Supriyanto Purwanjani (Yayasan Citra Dharma Cindekia, 2024)
Improper use of antibiotics will cause resistance in bacteria so that other alternatives are needed such as the use of avocado plants as antibacterial plants. To determine the antibacterial activity of avocado leaf ethanol extract on the growth of Staphylococcus aureus bacteria. Laboratory experimental research to see the antibacterial activity of ethanol extract and avocado leaf fractions with concentrations of 15%, 20% and 25%. Antibacterial activity tests were carried out using the disk diffusion method against Staphylococcus aureus and comparing the inhibition zones formed from each treatment with the positive control, namely Tetracycline. The inhibition power obtained was then analyzed using the One Way Anova statistical method. The content of 70% avocado leaf ethanol extract compounds consists of flavonoids, saponins, tannins, alkaloids and terpenoids. Face toner preparation of 70% ethanol extract of avocado leaves F1 (15%) has 11.5mm, F2 (20%) has 15.7 mm and F3 (25%) has 21.4% antibacterial activity against the growth of Staphylococcus aureus bacteria. Formula 3 with a concentration of 25% with an inhibition zone of 21.4 mm has the most optimal antibacterial activity against Staphylococcus aureus bacteria. The most optimal avocado leaf face toner preparation as an antibacterial activity for Staphylococcus aureus is a concentration of 25%.